Resilience of Crop Failure for Farmers in Dryland Area - Aoetpah, Ariel; Manafe, Rizky Pradita; Ratu, Feronika (Journal of Health and Behavioral Science, 2025)
Indonesia, as an agrarian country, is highly dependent on the agricultural sector, including in East Nusa Tenggara Province, which is dominated by dryland areas and prone to crop failure. The impact is not only economic but also psychological, such as stress and depression. Nevertheless, some farmers remain able to survive, demonstrating resilience. This study aims to describe the resilience and adaptive strategies of farmers in dryland areas using a qualitative phenomenological approach through in-depth interviews. The results show that resilience is shaped by family responsibility, land ownership, positive mindset, spiritual beliefs, self-confidence, and dependence on farming. Resilient farmers can manage emotions, think optimistically, and develop adaptive strategies. These findings are expected to serve as a foundation for policies to support the resilience of farmers in drought-prone areas.